A Review of the Flexural Behavior of Steel-Concrete Composite Beams Experimentally and Numerically - Al-Ani, Husam Khalaf; Hilal, Ameer A; Hama, Sheelan Mahmoud (Iraqi Journal of Civil Engineering, 2025)
Composite beams, made up of a concrete slab and steel in the IPE steel section, are commonly used in bridges and buildings. Their main function is to enhance structural efficiency by merging the compressive strength of concrete with the tensile resistance of steel, thereby improving overall stiffness, ductility, and load-bearing capacity. This study offers an extensive review of the flexural behavior of steel-concrete composite beams, focusing on the interplay of concrete strength, shear connector types, and interaction levels in determining structural performance. It integrates experimental and numerical research to analyze critical parameters, including load-deflection behavior, shear transfer efficiency, and crack propagation at the steel-concrete interface. The study emphasizes the effect of concrete compressive strength, particularly in ultra-high-performance concrete (UHPC) and lightweight concrete, on stiffness, ductility, and load-bearing capacity while reducing self-weight and enhancing sustainability. The study revealed that fully bonded shear connectors, using CFRP sheets and welded plates, enhance flexural capacity and stiffness. In contrast, partial bonding or pre-debonding reduces performance due to crack propagation. Indented and hot-rolled U-section connectors enhance interaction and minimize slip, while uniform distribution of shear connectors optimizes load capacity and stiffness. Lightweight concrete decreases slab weight without compromising performance, and high-performance materials such as ECC, SFRC, and UHPFRC improve strength and ductility. Numerical modeling, particularly finite element methods, and higher-order beam theories validate experimental results, providing accurate tools for predicting structural behavior under various loading and environmental conditions.